Developing A Territorial Approach to Wolves through Agri-food Practices. A Survey on the Relations Between Biodiversity and Food in Belledonne - Inès Creti; Edith Chezel; Coralie Mounet; Dominique Baud; Pauline Dusseux (Revue de Géographie Alpine)
Wolves’ return to France since 1992 highlights the contradictory injunctions and the overlooked theoretical and political ideas as regards the relationship between biodiversity and food that mountainous regions are faced with. Government and regulatory responses have not yet succeeded in overcoming the conflicts brought about by the presence of wolves in the day-to-day lives of those living in mountainous regions. How can we transition from a mere adaptation of national sectoral policies on a territorial scale to the development of an actual territorial approach to the conservation of biodiversity, while taking account of the experiences and needs of inhabitants and players, and the specific challenges faced by such territories as regards food? By conducting a survey on the role played by agropastoralism in the development of mountainous regions, and cross-examining biodiversity and food issues, our territorial approach hypothesis raises the question of a collective debate regarding the future of such regions. In this study, we explain the work carried out since 2019 in the context of a research-action-creation project in Belledonne – RECIBIOLDAL – which is based partly on a long-term survey attempting to understand the relations between biodiversity and food in terms of how the landscape has evolved since 1920, and partly on the creation of a narrative surrounding current farming and food practices, with a view to understanding relations between inhabitants, both human and non-human. Lastly, we will look into how the care afforded to these links and various relationships can contribute towards discussion surrounding a territorial approach to wolf and food management.